tìm x
(x-2)(x2 +2x +7) +2(x2 -4) -5(x-2)=0
Bài 3: Tìm x
1) ( x + 5)2 = (x + 3)( x – 7)
2) (x + 2)(x2 -2x + 4) = 15 + x(x2 +2)
3) x2 + 6x = -9
4) x3 - 9x2 = 27 – 27x
5) (2x + 1)2 - 4(x + 2)2 = 9
6) –x2 - 2x +15 = 0
\(1,\Leftrightarrow x^2+10x+25=x^2-4x-21\\ \Leftrightarrow14x=-46\\ \Leftrightarrow x=-\dfrac{23}{7}\\ 2,\Leftrightarrow x^3+8=15+x^3+2x\\ \Leftrightarrow2x=-7\Leftrightarrow x=-\dfrac{7}{2}\\ 3,\Leftrightarrow\left(x+3\right)^2=0\\ \Leftrightarrow x=-3\\ 4,\Leftrightarrow x^3-9x^2+27x-27=0\\ \Leftrightarrow\left(x-3\right)^3=0\\ \Leftrightarrow x-3=0\Leftrightarrow x=3\\ 5,\Leftrightarrow4x^2+4x+1-4x^2-16x-16=9\\ \Leftrightarrow-12x=24\Leftrightarrow x=-2\\ 6,\Leftrightarrow x^2-3x+5x-15=0\\ \Leftrightarrow\left(x-3\right)\left(x+5\right)=0\Leftrightarrow\left[{}\begin{matrix}x=3\\x=-5\end{matrix}\right.\)
Tìm x biết :
a, (x-2).(x2 +2x +7) +2.( x2-4) -5 .(x-2) =0
b, 4x2 -25 -(2x-5) .(2x+7) =0
c, x3 +27 + (x+3) .(x-9)=0
Tìm x, biết:
a) 3x(x - 1) + x - 1 = 0;
b) (x - 2)( x 2 + 2x + 7) + 2( x 2 - 4) - 5(x - 2) = 0;
c) ( 2 x - 1 ) 2 - 25 = 0;
d) x 3 + 27 + (x + 3)(x - 9) = 0.
a) x = 1; x = - 1 3 b) x = 2.
c) x = 3; x = -2. d) x = -3; x = 0; x = 2.
a) x2(x - 5) + 5 - x = 0; b) 3x4 - 9x3 = -9x2 + 27x;
c) x2(x + 8) + x2 = -8x; d) (x + 3)(x2 -3x + 5) = x2 + 3x.
e) 3x(x - 1) + x - 1 = 0;
f) (x - 2)(x2 + 2x + 7) + 2(x2 - 4) - 5(x - 2) = 0;
g) (2x - 1)2 - 25 = 0;
h) x3 + 27 + (x + 3)(x - 9) = 0.
i)8x3 - 50x = 0; k) 2(x + 3)-x2 - 3x = 0;
m)6x2 - 15x - (2x - 5)(2x + 5) =
a: \(\Leftrightarrow\left(x-5\right)\left(x+1\right)\left(x-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=5\\x=-1\\x=1\end{matrix}\right.\)
d: \(\Leftrightarrow\left(x+3\right)\left(x^2-4x+5\right)=0\)
\(\Leftrightarrow x+3=0\)
hay x=-3
a) 2x2 + 2x(5 - x)=12 d) 2(x + 5) - x2 - 5x = 0 g) (3x + 1)2 - (x+1) = 0
b) (5 - 2x)2 - 16 = 0 e) (2x - 1)2 - 4(x + 7)(x - 7) = 0 h) x2 + 7x - 8 = 0
c) 3x2 - 3x(x-2) = 36 f) (x + 4)2 - (x + 1)(x - 1) = 16 i) -2x2 +13x -15 = 0
mik cần gấp, cảm ơn mọi người.
\(a,\Leftrightarrow2x^2+10x-2x^2=12\Leftrightarrow x=\dfrac{12}{10}=\dfrac{6}{5}\\ b,\Leftrightarrow\left(5-2x-4\right)\left(5-2x+4\right)=0\\ \Leftrightarrow\left(1-2x\right)\left(9-2x\right)=0\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{1}{2}\\x=\dfrac{9}{2}\end{matrix}\right.\\ c,\Leftrightarrow3x^2-3x^2+6x=36\Leftrightarrow x=6\\ d,\Leftrightarrow2\left(x+5\right)-x\left(x+5\right)=0\\ \Leftrightarrow\left(2-x\right)\left(x+5\right)=0\Leftrightarrow\left[{}\begin{matrix}x=2\\x=-5\end{matrix}\right.\\ e,\Leftrightarrow4x^2-4x+1-4x^2+196=0\\ \Leftrightarrow-4x=-197\Leftrightarrow x=\dfrac{197}{4}\)
\(f,\Leftrightarrow x^2+8x+16-x^2+1=16\Leftrightarrow8x=-1\Leftrightarrow x=-\dfrac{1}{8}\\ g,Sửa:\left(3x+1\right)^2-\left(x+1\right)^2=0\\ \Leftrightarrow\left(3x+1-x-1\right)\left(3x+1+x+1\right)=0\\ \Leftrightarrow2x\left(4x+2\right)=0\Leftrightarrow\left[{}\begin{matrix}x=0\\x=-\dfrac{1}{2}\end{matrix}\right.\\ h,\Leftrightarrow x^2+8x-x-8=0\\ \Leftrightarrow\left(x+8\right)\left(x-1\right)=0\Leftrightarrow\left[{}\begin{matrix}x=1\\x=-8\end{matrix}\right.\\ i,\Leftrightarrow2x^2-13x+15=0\\ \Leftrightarrow2x^2+2x-15x-15=0\\ \Leftrightarrow\left(x+1\right)\left(2x-15\right)=0\Leftrightarrow\left[{}\begin{matrix}x=-1\\x=\dfrac{15}{2}\end{matrix}\right.\)
Bài 5. Tìm x , biết rằng: a) x(x + 5)(x – 5) – (x + 2)(x2 – 2x + 4) = 3
b) (x – 3)3 – (x – 3)(x2 + 3x + 9) + 9(x + 1)2 = 15
c) (x+5)(x2 –5x +25) – (x – 7) = x3
d) (x+2)(x2 – 2x + 4) – x(x2 + 2) = 4
`a) x(x + 5)(x – 5) – (x + 2)(x^2 – 2x + 4) = 3`
`<=>x(x^2-25)-(x^3-8)=3`
`<=>x^3-25x-x^3+8=3`
`<=>-25x=-5`
`<=>x=1/5`
`b) (x – 3)^3 – (x – 3)(x^2 + 3x + 9) + 9(x + 1)^2 = 15`
`<=>x^3-9x^2+27x-27-(x^3-27)+9(x^2+2x+1)=15`
`<=>-9x^2+27x+9x^2+18x+9=15`
`<=>45x+9=15`
`<=>45x=6`
`<=>x=6/45=2/15`
`c) (x+5)(x^2 –5x +25) – (x – 7) = x^3`
`<=>x^3-125-x+7=x^3`
`<=>x^3-x-118=x^3`
`<=>-x-118=0`
`<=>-x=118<=>x=-118`
`d) (x+2)(x^2 – 2x + 4) – x(x^2 + 2) = 4 `
`<=>x^3+8-x^3-2x=4`
`<=>8-2x=4`
`<=>2x=4<=>x=2`
Tìm x, biết
(x - 2)(x2 + 2x + 4) + 2(x2 - 4) - 5(x - 2) = 0
(x - 2)(x2 + 2x + 4) + 2(x2 - 4) - 5(x - 2) = 0
(x - 2)(x + 2)2 + 2(x - 2)(x+2) - 5(x - 2) = 0
(x - 2)[(x+2)2 + 2(x+2) - 5]= 0
(x - 2)[(x + 2)2 + 2(x + 2) + 1 - 6] = 0
( x - 2)[(x + 2 + 1)2 - 6] = 0
(x - 2)[(x + 3)2 - 6] = 0
(x - 2)(x + 3 - \(\sqrt{6}\))(x + 3 + \(\sqrt{6}\)) = 0
TH1. x - 2 = 0 <=> x = 2
TH2. x + 3 - \(\sqrt{6}\) = 0 <=> x = \(\sqrt{6}-3\)
TH3. x + 3 + \(\sqrt{6}\) = 0 <=> x = \(-\sqrt{6}-3\)
S = {2; \(\sqrt{6}-3\); \(-\sqrt{6}-3\)}
(x+2)(x2+2x+7)+2(x2-4)-5(x-2)=0
\(\left(x+2\right)\left(x^2+2x+7\right)+2\left(x^2-4\right)-5\left(x-2\right)=0\)
\(\Leftrightarrow\left(x+2\right)\left(x^2+2x+7\right)+\left(x-2\right)\left(2x+4\right)-5\left(x-2\right)=0\)
\(\Leftrightarrow\left(x+2\right)\left(x^2+4x+6\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x+2=0\\x^2+4x+6=0\end{matrix}\right.\)
Có: \(x^2+4x+6=x^2+2.2+2x+4+2=\left(x+2\right)^2+2\)
\(\Leftrightarrow\left(x+2\right)^2\ge0\forall x\Rightarrow\left(x+2\right)^2\ge2\forall x\Rightarrow x^2+4x+6\ge2\forall x\)
\(\Rightarrow x+2=0\)
\(\Rightarrow x=-2\)
Vậy \(x=-2\)
Tìm x biết rằng:
a) ( x 2 + 2x + 4)(2 - x) + x(x - 3)(x + 4) - x 2 + 24 = 0;
b) x 2 + 3 ( 5 − 6 x ) + ( 12 x − 2 ) x 4 + 3 = 0 .